2013
DOI: 10.1177/0093854812474425
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nonfatal Force on and by Persons With Apparent Mental Disorder in Encounters With Police

Abstract: Although a number of factors have been examined in relation to their effect on the prevalence and characteristics of police use of force, studies examining whether the person appeared to be mentally ill during the incident are lacking. Police recorded that 306 (7.2%) of the 4,267 people on whom they used force in Victoria, Australia, between 1995 and 2008 appeared to have a mental disorder. This group was more likely to threaten or use weapons on police and to have weapons used or threatened against them by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
0
29
0
2
Order By: Relevance
“…For example, detailed examination of a Victorian police use of force database (Kesic et al 2013a(Kesic et al , 2013b showed a significant over-representation of mood and anxiety disorders, psychosis, schizophrenia, substance use disorder and personality disorders with a high degree of comorbidity as compared to the estimated prevalence of these disorders in the general community (Short et al 2010).…”
Section: Research On Police Use Of Forcementioning
confidence: 99%
See 4 more Smart Citations
“…For example, detailed examination of a Victorian police use of force database (Kesic et al 2013a(Kesic et al , 2013b showed a significant over-representation of mood and anxiety disorders, psychosis, schizophrenia, substance use disorder and personality disorders with a high degree of comorbidity as compared to the estimated prevalence of these disorders in the general community (Short et al 2010).…”
Section: Research On Police Use Of Forcementioning
confidence: 99%
“…Indeed, studies have suggested that the presence of substance use is common in mental health crisis incidents and even considered to be the trigger of the incident by police in over one in five cases (Short et al 2013). When all of these elements are present together, the police are more likely to report to having to resort to using force to resolve the situation (Garner and Maxwell 2002, Police Complaints Authority 2003, Kesic et al 2013a, 2013b. Despite an increasing understanding of some of the common 'ingredients' of these potentially volatile situations, what remains unclear at this time is a detailed understanding of the decision-making behind the officer's decision to use force and how individual perceptions of dangerousness inevitably impact on this process.…”
Section: Research On Police Use Of Forcementioning
confidence: 99%
See 3 more Smart Citations